An Interferometric Reflectance Imaging Sensor for Point of Care Viral Diagnostics - Reddington, Alexander P. (2013)
The use of in vitro diagnostic devices is transitioning from the laboratory to the primary care setting to address early disease detection needs. Time critical viral diagnoses are often made without support due to the experimental time required in today’s standard tests. Available rapid point of care (POC) viral tests are less reliable, requiring a follow-on confirmatory test before conclusions can be drawn. The development of a reliable POC viral test for the primary care setting would decrease the time for diagnosis leading to a lower chance of transmission and improve recovery. The single particle interferometric reflectance imaging sensor (SP-IRIS) has been shown to be a sensitive and specific-detection platform in serum and whole blood. This paper presents a step towards a POC viral assay through a SP-IRIS prototype with automated data acquisition and analysis and a simple, easy-to-use software interface. Decreasing operation complexity highlights the potential of SP-IRIS as a sensitive and specific POC diagnostic tool. With the integration of a microfluidic cartridge, this automated instrument will allow an untrained user to run a sample-to-answer viral assay in the POC setting.